Gender disparity in school participation and achievement: the case in Malaysia - Mohd Jelas, Zalizan; Mohd Salleh, Amla; Mahmud, Mohd Izwan; Azman, Norzaini; Hamzah, Hanizah; Abdul Hamid, Zaleha; Jani, Rohana; Hamzah, Ramlah (Elsevier, 2014)
Gender differences with regard to academic performance remain one of the more challenging issues in educational research. Gender disparity in education has traditionally focus on the under participation of girls and still is in some parts of the world. In a number of countries, including Malaysia, gender disparity in basic and higher education are in favor of girls both in terms of participation and performance. The dual purpose of this paper is to address and to understand the nature of the issue by analyzing the trends of student participation and performance; and secondly, to seek whether student engagement and burnout are possible factors contributing to school dropout and low achievement. There are evidence in the literature to show student engagement and student burnout accounted for gender differences in school performance. The results of the analysis of secondary data reflected a trend that shows girls outperformed boys in national examinations across school levels and types. These trends are confirmed by results of a survey of the level of student engagement and student burnout on a sample of students aged 12, 14 and 16 which seems to suggest that boys are less engaged than girls, and experience more burnout. The findings are discussed in the context of developing support for students, particularly boys, to be more engaged, and less burnout in school and in learning.